A high-quality carrot genome assembly provides new insights into carotenoid accumulation and asterid genome evolution - Iorizzo, Massimo (2016)
We report a high-quality chromosome-scale assembly and analysis of the carrot (Daucus carota) genome, the first sequenced genome to include a comparative evolutionary analysis among members of the euasterid II clade. We characterized two new polyploidization events, both occurring after the divergence of carrot from members of the Asterales order, clarifying the evolutionary scenario before and after radiation of the two main asterid clades. Large- and small-scale lineage-specific duplications have contributed to the expansion of gene families, including those with roles in flowering time, defense response, flavor, and pigment accumulation. We identified a candidate gene, DCAR_032551, that conditions carotenoid accumulation (Y) in carrot taproot and is coexpressed with several isoprenoid biosynthetic genes. The primary mechanism regulating carotenoid accumulation in carrot taproot is not at the biosynthetic level. We hypothesize that DCAR_032551 regulates upstream photosystem development and functional processes, including photomorphogenesis and root de-etiolation.